CLINICAL AND DIAGNOSTIC CRITERIALS OF LIVER FIBROSIS FORMATION IN PATIENTS WITH CHRONIC VIRAL HEPATITIS C WITH EXTRAHEPATIVE MANIFESTATIONS - Narziyev I.I; Oblokulova O.A; Tohirov F.F (PT. Antis International Publisher, 2024)
Background: Chronic viral hepatitis C (CVHC) is often associated with various extrahepatic manifestations, which may complicate the disease's progression. Specific Background: Cryoglobulinemia, characterized by the presence of cryoglobulins in the blood, has been implicated in the exacerbation of liver conditions, yet its role in CVHC remains inadequately explored. Knowledge Gap: Despite existing knowledge of the relationship between cryoglobulinemia and liver disease, the specific impact of cryoglobulinemia on the severity of liver fibrosis and associated extrahepatic manifestations in CVHC patients requires further elucidation. Aims: This study aims to investigate the prevalence of extrahepatic manifestations and the extent of liver fibrosis in patients with CVHC who also present with cryoglobulinemia, thereby determining the clinical implications of cryoglobulin presence. Results: Our findings indicate that patients with cryoglobulinemia demonstrate a significantly higher prevalence of extrahepatic manifestations and advanced stages of liver fibrosis compared to those without cryoglobulinemia. Novelty: This research contributes novel insights into the aggravating role of cryoglobulins in the clinical course of CVHC, highlighting their potential as biomarkers for disease severity. Implications: These results underscore the need for enhanced clinical monitoring and tailored therapeutic approaches for CVHC patients with cryoglobulinemia, as their condition may predict a more severe disease trajectory and necessitate more aggressive management strategies.